Migraciones y desarrollo: hacia un marco teórico común y coherente - Carballo de la Riva, Marta; Echart Muñoz, Enara (Revista Española de Desarrollo y Cooperación, 2023)
This article analyses the evolution of some of the mayor theories in migration and development, and the beginnings of the concept of codevelopment, intending to find a coherent analytical framework. It is offered as well a picture of the current discourse, when migration and development, as a binomial set, is placed under international and European debates. Finally, this discourse is compared with the actual practice, which seams to forget too often vital elements in this field, as rights, integration and citizenship.